2021
DOI: 10.3390/molecules26041182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Capacities of Antarctic Macroalgae and Their Use for Nanoparticles Production

Abstract: Macroalgae are sources of bioactive compounds that are interesting from both a chemical and a medical point of view. Although their use in biomedicine has increased significantly in recent years, tests conducted to date have been mostly related to species from temperate latitudes, with the potential application of Antarctic biodiversity being minor. The wide variety of algae species present on Antarctic coastal areas can be a source of new antioxidants. Bearing this in mind, the brown macroalgae Desmarestia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Lastly, in the bands at 1200 and 1050 cm −1 , a reduction in intensity was observed. The results obtained for both seaweed are in accordance with other works that have proposed that the carbonyl group from proteins is able to bind metals, and, as a result, they could most possibly cap AuNPs and, thus, prevent agglomeration [ 20 , 21 , 62 ]. The modifications observed in the region of 1200–1000 cm −1 could indicate that sulfonic groups from polysaccharides are involved in metal binding.…”
Section: Resultssupporting
confidence: 90%
“…Lastly, in the bands at 1200 and 1050 cm −1 , a reduction in intensity was observed. The results obtained for both seaweed are in accordance with other works that have proposed that the carbonyl group from proteins is able to bind metals, and, as a result, they could most possibly cap AuNPs and, thus, prevent agglomeration [ 20 , 21 , 62 ]. The modifications observed in the region of 1200–1000 cm −1 could indicate that sulfonic groups from polysaccharides are involved in metal binding.…”
Section: Resultssupporting
confidence: 90%
“…There are some previous reports on the reducing power of this species; however, results are expressed as optical density [38] or as IC 0.5 [39], so a comparison is not possible. When comparing this result with the ones obtain for other brown seaweed aqueous extracts obtained and analysed by the same methods, it was observed that UP presents a lower reducing capacity than C. baccata [40], S. polyschides [41], S. muticum [42], D. antarctica [43], and D. menziesii [44]; nevertheless, this reducing capacity is sufficient to synthesize gold and silver nanoparticles. Other works also confirmed the observation that UP possesses the lowest reducing power among other brown seaweeds [45,46].…”
Section: Antioxidant Activitymentioning
confidence: 55%
“…Also, AgNPs are intended to transport electrons to the reactive media in order to neutralize the unstable DPPH free radicals ( Chandraker et al, 2022a ). Prior to the present study were the seaweed Ecklonia cava ( Venkatesan et al, 2016 ), Desmarestia antarctica , and Iridaea cordata ( González-Ballesteros et al, 2021 ) mediated AgNPs studied for their antioxidant activity and provided similar results.…”
Section: Discussionmentioning
confidence: 87%